Lignin-based thermoresponsive macromolecules via vitamin-induced metal-free ATRP. (26th March 2021) - Zaborniak, I.; Macior, A.; Chmielarz, P.; Caceres Najarro, M.; Iruthayaraj, J.
Abstract: An environmentally-friendly process for the modification of lignin with thermoresponsive polymers was employed, providing well-defined structures with narrow molecular weight distribution ( M w / M n = 1.44). We report a biocompatible vitamin-inspired photoinitiation system composed of two components i.e. riboflavin (vitamin B2 ) as a photosensitizer and ascorbic acid (vitamin C) as a mild reducing agent. Under blue light LEDs irradiation at 460 nm (5.0 mW cm −2 ) the presented two-component photoinitiation setup enables grafting of poly(ethylene glycol) methyl ether methacrylate (OEGMA500 ) from brominated lignin via metal-free ATRP approach. A series of cyclic voltammetry (CV) measurements were conducted to electrochemically characterize ATRP initiators, both brominated lignin and lignin-based polymers, confirming preserved chain-end functionality of the prepared macromolecules. Received polymers with lignin core and POEGMA side chains exhibited thermoresponsive properties, which were investigated by determination of number average sizes of macromolecules by dynamic light scattering (DLS) and transmittance by ultraviolet/visible (UV-Vis) absorption spectroscopy of KL- g -(POEGMA-Br)10 aqueous solution. The in vitro curcumin release studies showed that the active substance is released from drug-loaded micelles in a thermo-sensitive manner. Prepared lignin-based macromolecules will show wide application as crucial components of thermoresponsive coatings, potentially creating bioactive surfaces characterized by antifouling properties, controlling cell adhesion or used as biosensors, due to PEG-containing side chains in branched polymers. Graphical abstract: Image 1 Highlights: Vitamin B2 and vitamin C as a biocompatible photoinitiation system in metal-free ATRP Thermoresponsive lignin-based polymers by a facile and eco-friendly approach Preserved chain-end fidelity of polymers confirmed by electrochemical characterization In vitro curcumin release from lignin-based micelles ensured in a thermo-sensitive manner